Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1158/1055-9965.epi-08-0544
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Negative Breast Cancer and Obesity in a Rural Appalachian Population

Abstract: Background Our objective was to determine the clinicopathologic features of triple-negative (estrogen receptor, progesterone receptor, and human epidermal growth factor-2 receptor negative) breast cancer and their relationship to obesity in women drawn from a population with one of the highest obesity rates in the United States. Methods This retrospective study involved 620 White patients with invasive breast cancer in West Virginia. Hospital tumor registry, charts, and pathology records provided age at diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 40 publications
7
89
2
Order By: Relevance
“…In our study, ER negative, PR negative and Her2/neu negative receptors constituted 13.2 % of our cases. In previous Indian study revealed 25 % cases of triple-negative breast cancer whereas Western countries have showed 14-30 % of triplenegative breast cancer [9,[31][32][33][34][35]. The negative expressions of triple receptors vary markedly with ethnicity and reported higher in African women as compared to White women [31].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, ER negative, PR negative and Her2/neu negative receptors constituted 13.2 % of our cases. In previous Indian study revealed 25 % cases of triple-negative breast cancer whereas Western countries have showed 14-30 % of triplenegative breast cancer [9,[31][32][33][34][35]. The negative expressions of triple receptors vary markedly with ethnicity and reported higher in African women as compared to White women [31].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, an increasing body of retrospective studies based on population analyses suggests that the incidence of obese TNBC patients is higher compared with that of non-obese patients. A retrospective study investigated 620 Caucasian patients with invasive breast cancer in West Virginia, among whom obesity was present in 49.6% of the Triple-negative breast cancer and its association with obesity (Review) TNBC patients, but in only 35.8% of the non-TNBC patients (P=0.0098) (8). Another study of clinicopathological data obtained from 112 TNBC patients in a Turkish hospital over a 5-year period reported that 30 (26.8%) were normoweight or underweight, and 82 (73.2%) were overweight/obese at the time of diagnosis (9).…”
Section: Obesity and Clinical Issues In Tnbc Patientsmentioning
confidence: 99%
“…4,5 TNBCs are predominantly diagnosed in younger women as well as women who are either African-American, 6,7 Hispanic, 8 or obese. 9,10 Furthermore, these cancers are more aggressive and poorly differentiated, and thus women with TNBC have a worse prognosis compared to other types of breast cancer. 4,11 These patients usually respond well to standard chemotherapy.…”
Section: Introductionmentioning
confidence: 99%